Incidence of the Metabolic Syndrome among Patients with Epilepsy Attending a Neuropsychiatric Hospital in Kigali, Rwanda - Ndayambaje, François Xavier; Gahutu, Jean Bosco; Rugera, Simon Peter; Natukunda, Bernard (International Journal of Current Science Research and Review, 2021)
Background & Aims: Metabolic syndrome (MetS), a combination of diverse metabolic disorders (hypertension, diabetes mellitus, high triglycerides, increased waist circumference, and low high density cholesterol, HDLc), is a well-known public health problem worldwide, and its prevalence is increasing dramatically. MetS is a confirmed great risk factor for cardiovascular diseases. Presently, limited information exists about incidence and the risk factors associated with metabolic syndrome (MetS) in patients with epilepsy. We prospectively estimated the incidence of MetS in patients with epilepsy. Methods: We recruited 322 participants, 161 patients with epilepsy and 161 healthy volunteers all of them free of any MetS criteria at the baseline and followed-up them for one year. New onset cases of MetS were defined according to the updated National Cholesterol Education Program (NCEP) Adult Treatment Panel III (ATPIII) criteria. Results: Over a 1-year follow-up, we observed 8 incident cases of MetS (7 individuals in patients group and 1 individual in control group) resulting in an annual cumulative incidence rate of 2.5%. We observed 9 cases losses to follow up. Patients with epilepsy presented a higher risk of developing MetS (RR=7.00, 95% CI: 0.891 - 1.67, p=0.032) than in control group. Sedentariness was associated with higher risk for MetS (hazard ratio, HR=6.537, 95%; confidence interval, C.I=1.269-33.685, p value =0.025. Conclusion: Anti-epileptic therapy combined with sedentariness increases the risk of developing MetS among patients with epilepsy. Holistic clinical management of patients with epilepsy will significantly contribute to MetS prevention
Keywords: Metabolic syndrome; Epilepsy; Incidence; Anti-epileptic drugs